'n Fantasietema-analasie van Maas se artikel 666 is net 'n syfer - Terblanche, Lydie; Jordaan, Danie (Department of Communication Science, University of the Free State, 2011)
Given the reality of persuasive communication practices in South Africa, the question arises as to which rational and/or non-rational characteristics of the contents of rhetorical messages contribute to the way in which recipients of such messages are so dramatically affected by them that they are motivated to display certain behaviour. It would seem that the symbolic convergence theory (SCT), along with its methodology, fantasy theme analysis (FTA), as developed by Bormann (1972) and his colleagues, is especially appropriate to explain this phenomenon. The identification and observance of a comparatively large number of possible phases in FTA aids the critic in his/her task to acquire the skills and proficiencies that are essential for the analysis of fantasy themes. On close examination rhetorical criticism is an art form that “requires” a competent rhetorical critic to display a unique approach, as well as the application of his/her own creative insights in the analysis of symbolic realities. Based on the principles of FTA, this article gives an indication as to why Deon Maas, with reference to his article 666 is net 'n syfer, is regarded as a controversial figure. In particular, an investigation is carried out in respect of the role played by the chaining out of fantasy themes in the creation of a rhetorical vision and the motivation of behaviour relating to the events surrounding the Maas article.
Keywords: Symbolic convergence theory (SCT); Fantasy theme analysis (FTA); Maas, Deon